2018
DOI: 10.20517/cdr.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Antibody drug conjugate development in gastrointestinal cancers: hopes and hurdles from clinical trials

Abstract: Gastrointestinal (GI) cancers represent the leading cause of cancer-related mortality worldwide. Antibody drug conjugates (ADCs) are a rapidly growing new class of anti-cancer agents which may improve GI cancer patient survival. ADCs combine tumour-antigen specific antibodies with cytotoxic drugs to deliver tumour cell specific chemotherapy. Currently, only two ADCs [brentuximab vedotin and trastuzumab emtansine (T-DM1)] have been Food and Drug Administration approved for the treatment of lymphoma and metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…The safety profile of RC48 was consistent with what would be expected of a HER2-targeted antibody–drug conjugate that uses monomethyl auristatin E as its payload [ 10 ]. The most common classes of treatment-related adverse events were gastrointestinal disorders, hematological toxicities, and nerve toxicities.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The safety profile of RC48 was consistent with what would be expected of a HER2-targeted antibody–drug conjugate that uses monomethyl auristatin E as its payload [ 10 ]. The most common classes of treatment-related adverse events were gastrointestinal disorders, hematological toxicities, and nerve toxicities.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, unlike T-DM1 with minimal bystander effect on nearby cells due to poor membrane permeability, RC48 has a bystander effect which can reverse T-DM1 resistance by acting on populations of cells not overexpressing HER2 [ 16 , 21 ]. Despite the failure of T-DM1 in gastric cancer, several other antibody–drug conjugates are under investigation, varying in antibody and linker payload [ 10 , 22 , 23 ]. There are currently six HER2 directed ADCs in varying stages of clinical development in patients with HER2 overexpressing gastrointestinal malignancies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also less effective substrates of drug resistance transporters [7]. Although tubulin inhibitors showed robust activity through a substantial number of clinical trials, a modest response rate was observed in the colon and gastric tumors [8].…”
Section: Editorial Mysliwymentioning
confidence: 99%